Genetically Improved Clonal Planting Stock of Eucalyptus - a Success Story from India - Lal, Piare; Kulkarni, H. D.; Srinivas, K.; Venkatesh, K. R.; Kumar, P. Santha (Indian Forester, 1997)
The paper describes success story of Clonal Technology Research and Development Programme for genetic improvement of planting stock of Eucalypts through vegetative propagation and cloning techniques being implemented since 1989. Comparative data in respect of adaptability and growth rates has been presented and discussed. Details of most promising clones called 'Bhadrachalam' clones of Eucalypts selected for large scale commercial multiplication, with their origin and performance in various trials have been given. Progress of Eucalypt plantations, major constraints and factors contributing to success have been described. Development and deployment of genetically improved, high yielding, fast growing and disease resistant 'Bhadrachalam' clones of Eucalyptus on commercial scale for the first time in India, by a private sector company, ITC Bhadrachalam Paperboards Limited, have been highlighted.